2018
DOI: 10.1590/1678-457x.34116
|View full text |Cite
|
Sign up to set email alerts
|

Influence of drying process on total phenolics, antioxidative activity and selected physical properties of edible bolete (Phlebopus colossus (R. Heim) Singer) and changes during storage

Abstract: The research aimed to study the effect of hot-air drying on the properties of edible bolete mushroom (Phlebopus colossus (R. Heim) Singer). Fresh edible bolete contained an efficient antioxidant activity, showing a significant value of total phenolic content and radical scavenging activity and was high in protein and fiber with low fat content. The changes in physicochemical and antioxidative properties of edible bolete during hot-air drying at various temperature and time were studied. The phenolic content an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
(21 reference statements)
3
7
1
Order By: Relevance
“…Fresh TBB samples contained a moisture content of 82.7 ± 2.0% on a wet-weight basis. Our results agreed with the findings of previous studies that found that the moisture content in fresh bolete mushrooms ranged from 70% to 93% depending upon the bolete species [ 43 , 44 , 45 , 46 , 47 ]. To extend the availability and shelf-life of TBB, a preservation method is recommended.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Fresh TBB samples contained a moisture content of 82.7 ± 2.0% on a wet-weight basis. Our results agreed with the findings of previous studies that found that the moisture content in fresh bolete mushrooms ranged from 70% to 93% depending upon the bolete species [ 43 , 44 , 45 , 46 , 47 ]. To extend the availability and shelf-life of TBB, a preservation method is recommended.…”
Section: Resultssupporting
confidence: 93%
“…Our results are similar to those of previous studies that reported that the methanolic extract of ECM mushrooms, including boletes, revealed notable DPPH, ABTS, and FRAP activities [ 13 , 14 , 47 , 60 , 61 ]. The results indicate that different preservation methods affected the antioxidative activities of the samples.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…portentosus and Ph. colosus, phenolic compounds were determined (Kaewnarin, Suwannarach, Kumla, & Lumyong, 2016;Liaotracoon & Liaotracoon, 2018). Therefore, exudates of Ph.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, interest in fungi has jumped considerably due to their richness in phenolic compounds, tocopherols and carotenoids, considered to be the most responsible for antioxidant activity. In addition to antioxidant capacity, this diversity of biomolecular compounds in wild edible fungi is also responsible for other biological activities; namely, antibacterial, antifungal, anti-inflammatory, antitumor and antiviral properties (Aprotosoaie et al, 2017;Liaotrakoon and Liaotrakoon, 2018). These compounds can be involved in the protection against various diseases, due to their antioxidant potential (Silva et al, 2004).…”
Section: Introductionmentioning
confidence: 99%